2022
DOI: 10.3389/fnut.2022.821924
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Immunonutrition in Head and Neck Cancer Patients Undergoing Cancer Treatment – A Systematic Review

Abstract: Background and AimsMalnutrition is prevalent among head and neck cancer (HNC) patients and leads to undesirable outcomes such as reduced treatment response and increased treatment-related side effects. This systematic review summarizes the recent evidence regarding the effect of immunonutrition in HNC patients undergoing radiotherapy and chemotherapy.MethodsA literature search was conducted of the CENTRAL, ProQuest, MEDLINE, EBSCOhost, Web of Science and CINAHL databases; and further supplemented with internet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
0
10
0
3
Order By: Relevance
“…Tan et al conducted a meta-analysis involving 1535 patients with HNSCC and revealed that immunonutrient-enriched supplements may decrease the severity of oral mucositis and improve overall nutrition status during radiotherapy and chemotherapy. 45 In addition, a meta-analysis involving 202 780 patients with cancer advocated using nonsteroidal anti-inflammatory drugs to decrease the risk of distant metastasis regardless of whether it is used before or after the cancer diagnosis. 46 On the basis of these findings, patients with a high mGPS may benefit from careful personalized treatment to improve their quality of life and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al conducted a meta-analysis involving 1535 patients with HNSCC and revealed that immunonutrient-enriched supplements may decrease the severity of oral mucositis and improve overall nutrition status during radiotherapy and chemotherapy. 45 In addition, a meta-analysis involving 202 780 patients with cancer advocated using nonsteroidal anti-inflammatory drugs to decrease the risk of distant metastasis regardless of whether it is used before or after the cancer diagnosis. 46 On the basis of these findings, patients with a high mGPS may benefit from careful personalized treatment to improve their quality of life and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of twenty studies indicated that immunonutrient-enriched formulas in HNC patients during chemo-radiation may have a positive impact on maintaining nutrition status. (32) In another review paper, Immunonutrition showed to reduce postoperative fistula formation, but there was no other positive outcome on length of hospital stay, wound infection, and adverse events. (51) In a systematic search of oral or enteral immunonutrition versus standard nutrition, Miller et al concluded that there is insufficient evidence on the beneficial effects of immunonutrition on infectious episodes in heterogeneous populations including HNC patients during chemotherapy.…”
Section: Moderate Consensusmentioning
confidence: 99%
“…In a Randomized Control Trial (RCT), 37 ambulatory post-operative HNC patients showed improvement in blood protein concentration and lymphocyte levels after they consumed nutritional supplements enriched with omega-3 fatty acids (31) In a systematic review, five out of seven studies reported a beneficial effect of omega-3 enriched Immunonutrient formula on the nutritional status of HNC patients by reducing treatment toxic effects. (32) Studies strongly indicate that ω3 PUFA increases nutrient intake and has a significant role in improving increasing body weight and body composition in cancer patients. (33)(34)(35)(36)(37)(38)(39) Couple of studies have demonstrated the protective effect of omega-3 fatty acids on chemo-induced neuropathy.…”
Section: Moderate Consensusmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some systematic reviews explored the modulatory role of omega-3 in patients with head and neck cancer, [ 18 ] surgery for gastrointestinal malignancy, [ 19 ] prostate cancer, [ 20 ] and lung cancer undergoing radiotherapy and chemotherapy, [ 21 ] there had been no evidence of its role in the nutritional status of patients with pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%